Assessing Postsurgical Outcomes with Prepectoral Breast Reconstruction: A Literature Review and Meta-analysis Update. Issue 10 (26th October 2021) - Chatterjee, Abhishek; Nahabedian, Maurice Y.; Gabriel, Allen; Sporck, Michael; Parekh, Mousam; Macarios, David; Hammer, Jason; Sigalove, Steven
Abstract : Background: Prepectoral implant-based breast reconstruction is an alternative to subpectoral/dual-plane reconstruction. Methods: This study examined outcomes of prepectoral reconstruction using a meta-analysis of data pooled with data from our previous review. Thirty studies were included. Results: Explantation, seroma, and infection were the most common complications with no animation deformity reported. Significantly lower odds of infection were observed with prepectoral compared with dual-plane reconstruction. Conclusions: Current literature suggests that prepectoral reconstruction may be associated with lower rates of postsurgical infections.